KRISIS SOSIO-KULTURAL DAN KESADARAN HUKUM MASYARAKAT KOTA BANDA ACEH - Sani, Abdullah; Muhibbuthabry, Muhibbuthabry (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2020)
Banda Aceh is one of the cities in Aceh Province which is classified as a heterogeneous population, in addition to being caused by its position as the capital of Aceh Province, Banda Aceh is also known as a student city and a business city and a major tourist destination. Of the 259,913 inhabitants of Banda Aceh in 2018, they came from various ethnicities and even different religions. In addition, there are several non-Muslim houses of worship, there are also no strict rules governing residences. As a result of community, traffic is less regular, so that opportunities are open for various kinds of violations of the law and crime rates. But there is one interesting thing in Banda Aceh, even though the population is heterogeneous from various ethnic and religious lines, the role of local residents (indigenous people) is not too prominent. In Banda Aceh, the primordial system did not occur as in other regions. The life of the people who are aware of diversity is exemplary, but this does not mean that the negative side and social crisis are not at all. The results of the study found that crisis socio-cultural and legal awareness in Banda Aceh was rather alarming and needed government attention early on. Promiscuity, hanging out in cafes until late at night, even into the morning is a new culture that denies the values ​​of education. Another wrong or mistaken culture is infected with a culture of lazy learning scientifically, a culture of materialist life, and scolding greetings by using the Islamic version of greetings gradually starting to be abandoned. The methodology used in this study is qualitative descriptive.